2022
DOI: 10.1186/s12889-022-13378-4
|View full text |Cite
|
Sign up to set email alerts
|

Current status and influencing factors of digital health literacy among community-dwelling older adults in Southwest China: a cross-sectional study

Abstract: Background The rapid development of digital health has reduced the time and cost of medical treatment, bringing efficient and economical benefits. However, older adults all over the world are deficient in digital health knowledge and skills to varying degrees. This study intends to investigate the current status and influencing factors of digital health literacy among community-dwelling older adults in Southwest China, so as to provide theoretical reference for global digital health researches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
(62 reference statements)
0
20
0
1
Order By: Relevance
“…Other studies have shown similar results in Chinese population. Liu et al 17 studied an elderly population in China and found that female sex is one of the major risk factors associated with low health knowledge. Pan et al 18 conducted a survey in northwest China of stroke patients' health knowledge and also got similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown similar results in Chinese population. Liu et al 17 studied an elderly population in China and found that female sex is one of the major risk factors associated with low health knowledge. Pan et al 18 conducted a survey in northwest China of stroke patients' health knowledge and also got similar results.…”
Section: Discussionmentioning
confidence: 99%
“…This association was also identified by Knapp et al [ 53 ]; older age was correlated with lower levels of agreement on the eHEALS. This can be explained by the fact that older adults have very limited acceptance and application of digital health [ 54 , 55 ] because they have difficulty navigating the internet and knowing which resources to trust [ 56 ] and turning the internet health knowledge into action and applying it to health self-management [ 57 ]. The lack of eHealth literacy has become a major impediment preventing older adults from integrating into the digital society and benefiting from convenient and efficient eHealth services [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that older adults have very limited acceptance and application of digital health [ 54 , 55 ] because they have difficulty navigating the internet and knowing which resources to trust [ 56 ] and turning the internet health knowledge into action and applying it to health self-management [ 57 ]. The lack of eHealth literacy has become a major impediment preventing older adults from integrating into the digital society and benefiting from convenient and efficient eHealth services [ 57 ]. It is imperative to improve older adults’ perceptions of the usefulness, ease of use, and reliability of eHealth services and to reduce their perception of eHealth-related risks [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Somente 35% demonstraram ter problema com a literacia em saúde, ressaltando que quanto maior o grau de escolaridade, maior a renda e, consequentemente, a literacia em saúde (Gustafsdottir et al, 2022). Corroborando com esses achados, em uma pesquisa referente aos fatores que influenciam a literacia em saúde entre os idosos com média de idade de 70,93 anos de uma comunidade do sudoeste da China, em que 67,83% dos participantes tinham apenas o ensino médio ou inferior, constataram que a literacia em saúde digital dos idosos era relativamente baixa (Liu et al, 2022). Na sociedade contemporânea, são mais de 4,5 bilhões de usuários da internet ao redor do mundo, o que corresponde a 58,8% da população mundial (Internet World Stats, 2019).…”
Section: Discussionunclassified